The Impact of Drug Abuse and Delinquency on Educational Environment Security - Vera V. Orlova; Larisa V. Shevchenko (Ital Publication, 2023)
Creating and maintaining a secure and supportive educational environment is essential for the success and well-being of university students. This study investigates the interplay between drug abuse, delinquency, sociocultural factors, and the security of the educational environment. Drawing upon a sample of 356 students from the Federal State-Funded Institution of Higher Education—Tomsk State University of Control Systems and Radioelectronics (TUSUR), we employed a partial least squares structural equation modeling (PLS-SEM) approach to analyze the data. The findings indicate that sociocultural security significantly influences students' behavioral intentions, with a confirmed negative impact on the intention to commit delinquency (β = -0.461, p < 0.05). Additionally, student well-being demonstrates a significant negative relationship with the intention to use drugs (β = -0.583, p < 0.01) and the intention to commit delinquency (β = -0.714, p < 0.001). However, the impact of sociocultural security and well-being on the intention to use drugs was not confirmed (β = -0.731, p > 0.05). Furthermore, the study reveals that students' behavioral intentions significantly affect the security of the educational environment. The intention to use drugs and the intention to commit delinquency negatively impact the security of the educational environment (β = -0.635, p > 0.05; β = -0.660, p < 0.05, respectively). These findings contribute to the understanding of the complex dynamics that shape the educational environment in universities. The study highlights the importance of promoting sociocultural security and fostering student well-being to prevent negative behavioral intentions and maintain a secure learning environment. Doi: 10.28991/ESJ-2023-07-05-018 Full Text: PDF